Lean and Green Supply Chain Management Optimization Models and Algorithms - Paksoy, Turan; Weber, Gerhard-Wilhelm; Huber, Sandra (International Series in Operations Research & Management Science, 2019)
This book presents the latest developments in optimization and optimal control models; exact, approximate and hybrid methods; and their applications in lean and green supply chains. It examines supply chain network design and modeling, closed loop supply chains, and lean, green, resilient and agile or responsive networks, and also discusses corporate social responsibility and occupational health and safety. It particularly focuses on supply chain management under uncertainty - employing stochastic or nonlinear modeling, simulation based studies and optimization - multi-criteria decision-making and applications of fuzzy set theory, and covers various aspects of supply chain management such as risk management, supplier selection or the design of automated warehouses. Lastly, using experimental applications and practical case studies, it shows the impact of lean and green applications on vehicle/fleet management and operations management.